Analisis Pengaruh Gratifikasi Sosial Media TikTok terhadap Transactive Memory System (TMS) dalam Adopsi Informasi Kesehatan Obesitas - Cahyaningtyas, Astri; Hidayanto, Achmad Nizar (The Indonesian Journal of Computer Science, 2024)
Obesity has become a global issue with increasing prevalence across various age groups, including children and adults. Obesity increases the risk of non-communicable diseases such as diabetes, heart disease, and cancer. Accurate health information is crucial for the prevention and management of obesity in Indonesia. However, the dissemination of inaccurate information on social media platforms like TikTok poses significant challenges. This study analyzes the motivation behind the adoption of health information via TikTok by integrating the Uses and Gratification Theory (UGT) and the Transactive Memory System (TMS). Data were collected from 255 respondents through an online questionnaire. The data were analyzed using SmartPLS with PLS-SEM. The results of the study indicate that gratifications such as social interaction and personalization have a significant influence on all dimensions of TMS. Furthermore, all three dimensions of TMS significantly impact information adoption. These findings provide insights into the utilization of TikTok for health education related to obesity in Indonesia.